Funding change: An environmental scan of research funders' knowledge translation strategic plans and initiatives across 10 high-income countries/regions - Christine Fahim; Danielle Kasperavicius; Robyn Beckett; Keelia Quinn de Launay; Arthana Chandraraj; Amanda Crupi; Suvabna Theivendrampillai; Sharon E. Straus (Canadian Science Publishing, 2023)
Knowledge translation (KT) is the science and practice of dissemination and implementation of evidence. We describe how research funders operationalize and evaluate KT initiatives, identify challenges and opportunities, and suggest strategic considerations for KT support. We conducted an environmental scan, which included a systematic search of published and grey literature and a focus group with Canadian funders. A total of 130 published articles and 2415 grey literature sources were screened; 212 unique data sources were included. Published literature commonly described KT initiatives related to "KT practice and science funding." These initiatives commonly provided funds for infrastructure development (e.g., clinical technologies, database subscriptions) to facilitate translational or applied research to address regional health priorities. Of the articles, 44% outlined an evaluation plan; few provided validated KT metrics. In the grey literature, 364 initiatives were described; the most commonly described initiatives related to "exchange and integrated KT." Focus group participants hoped to see increased resources to support KT, exchange opportunities with policy/decision-makers, and evaluate KT initiatives. Funders completed various KT initiatives, which tended to engage stakeholders to set research priorities, collaborate with a range of stakeholders, build KT capacity, and mandate KT requirements. We provide six considerations for funders to support KT.